A Preliminary Study on Sympathetic Skin Response in Acute Ischemic Cerebrovascular Disease - Chen W; Chen Y; Ye W; Wang T (International Journal of General Medicine, 2023)
Wenhong Chen,1 Yunping Chen,2 Wenjuan Ye,3 Ting Wang1 1Department of Pediatric Neurology, Maternal and Child Health Hospital of Hubei Province, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Neurology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 3Department of Pediatric, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of ChinaCorrespondence: Ting Wang, Department of Pediatric Neurology, Maternal and Child Health Hospital of Hubei Province, Tongji Medical College, Huazhong University of Science and Technology, 745 Wuluo Road, Hongshan District, Wuhan, Hubei, People’s Republic of China, Tel +86-27-87169308, Email 67722896@qq.comPurpose: The study aims to identify the characteristics of SSR in patients with AICVD and their correlation with clinical presentations.Methods: SSR of the upper limbs, the National Institute of Health stroke scale (NIHSS), the Barthel index (BI), the Essen stroke risk score (ESRS), and imaging examinations, was evaluated in 30 healthy subjects and 66 patients with AICVD. All results were recorded and analyzed via Statistical Package for the Social Sciences (SPSS 22.0) software. t-test and Spearman rank correlation were used.Results: Compared to the control group, SSR of upper limbs in patients with AICVD showed prolonged latency, reduced amplitude, and disappeared waveform (p=0.000, p=0.015, p=0.004), No statistically significant difference was observed between the affected side and the healthy side (p=0.068, p=0.661). In the case group, the higher the abnormal rate of SSR, the more severe the neurological impairment (NIHSS and ADL scores) and the worse the long-term prognosis. Specific results are as follows: Firstly, the total abnormality rate of SSR, prolonged SSR latency were positively related to the NIHSS, also the ESRS (r=0.347, p=0.004; r=0.437, p< 0.001), (r=0.371, p=0.005; r=0.433, p=0.001), the reduced amplitude was positively related to the NIHSS (r=0.341, p=0.012) while the disappeared waveform was positively related to the ESRS (r=0.299, p=0.015); Secondly, the total abnormality rate of SSR, prolonged SSR latency and reduced amplitude were negatively related to the BI (r=− 0.346, p=0.004) (r=− 0.426, p=0.001) (r=− 0.316, p=0.020).Conclusion: There may be inhibition of sympathetic reflex activity in patients with AICVD, SSR abnormality rate in patients with AICVD may be correlated with the degree of neurological impairment and long-term prognosis.Keywords: acute ischemic cerebrovascular disease, AICVD, sympathetic skin response, SSR, autonomic nervous system, ANS